Effects of the COVID-19 pandemic on the mental health of rehabilitation area professionals: A systematic review - Bohórquez-Blanco, Sandra; Allande-Cussó, Regina; Martín-López, Cristina; Gómez-Salgado, Juan; García-Iglesias, Juan Jesús; Fagundo-Rivera, Javier; Ruiz-Frutos, Carlos (Frontiers in Public Health, 2022)
Background: The role of the physiotherapist is vital in the recovery of post-COVID-19 patients, but fear of contagion is a possible feeling among healthcare professionals. The objective of this study is to assess the mental health effects that COVID-19 has had on healthcare workers, including rehabilitation care, in times of pandemic. Methods: A systematic review was conducted using the PRISMA format in the Pubmed, SCOPUS, and Web of Science databases between July and September 2022. Keywords included were ‘healthcare providers’, ‘COVID-19’, ‘Mental Health’, and ‘Psychological Distress’. Methodological quality was assessed using the Joanna Briggs Institute critical appraisal tools. Results: A total of 14 studies were included in this review. The study population was healthcare professionals including the rehabilitation services. In total, 4 studies reported exclusively on anxiety and stress levels in physiotherapists providing care during the pandemic. Conclusions: The mental health of healthcare professionals has been compromised during the pandemic. However, initially, research was only focused on physicians and nurses, so the need arises to include those professionals, such as physiotherapists, who are also in direct contact with COVID-19 patients.